THE ROLE OF THE EFFECTIVENESS OF MSMES IN INCREASING COMMUNITY INCOME IN PEMATANG SERAI VILLAGE - Hasanah, Uswatun; Annisa Ilmi Faried; Sebayang, Saimara AM; Nisa Ulzannah (Journal of Development Economics and Digitalization, Tourism Economics, 2024)
This study analyzes the role and effectiveness of UMKM (Micro, Small, and Medium Enterprises) in increasing community income in Desa Pematang Serai, Langkat, using a SWOT analysis and scoring approach. The findings reveal key strengths, such as the diversity of local products, the provision of job opportunities, and low operational costs due to the use of local resources. Major weaknesses include limited access to technology, insufficient business capital, and a lack of structured management. Opportunities identified include growing market awareness of local products, governmental and financial support, and the potential for digital market expansion. However, threats, such as competition from external products, fluctuations in raw material prices, and economic instability, pose challenges to UMKM growth.The weighted scores indicate that strengths have the most significant impact, with a total score of 3.30, emphasizing the potential for UMKM to boost local economic growth. Weaknesses scored a total of 2.75, indicating the need for improvements in technology access, financial support, and management. Opportunities, with a score of 2.50, highlight the importance of utilizing government support and digital marketing. Threats scored the lowest at 1.80, though they underscore the need for UMKM to adapt to external pressures. Overall, this analysis underscores the importance of supporting UMKM through improved financing, training, and sustainable practices to optimize their role in enhancing rural income.